Research of the Virtual Test Method for Dynamic Load Simulation of Automatic Transmission - Zou Xihong; Gou Xun; Zheng Xiaomei; Zhao Jun (Jixie chuandong)
The dynamic load simulation is a key technology of indoor bench test and an important assessment of automatic transmission performances. In order to achieve EM-CVT dynamic load simulation,the dynamic load simulation method is researched by using MATLAB/Simulink to establish the mathematical model of automatic transmission dynamic load simulation system and combining with the speed tracking control algorithm.The virtual test is carried out,which refers to a section of the NEDC city cycle,the EPA performance index is introduced to evaluate the system performance. The results show that the motors can response to speed and torque instruction of model rapidly,the system can run smoothly,the maximum relative errors of rotational speed and torque are 1% and 8%,the standard errors of estimate（ SE） and the coefficients of determination（ r2） of speed and torque are 4. 3 r/min,17. 7 N·m and 0. 99,0. 91,it has a better performance than EPA performance index.